Financial Accountability Dimensions Of Islamic Values At Al Washliyah Higher SCHO - Nawir Yuslem; Nurlaila Nurlaila; Yurmaini Yurmaini (Eduvest - Journal of Universal Studies, 2021)
The problem behind this research is that ideally the financial accountability of Islamic organizations including educational institutions must uphold Islamic values. But in reality, there are still many Islamic educational institutions that have not made Islamic values ​​the basis for managing the financial system. Al Jam'iyatul Washliyah as a community organization based on Islamic teachings manages several universities, where financial management and accountability are required to be based on Islamic values. The formulation of this research is how financial accountability has the dimensions of Islamic values ​​at Al Washliyah College in North Sumatra. This research is a qualitative research with a phenomenological approach, while the paradigm used is an interpretive paradigm. Data collection methods are interviews, observation and documentation. The data sources of this research are primary and secondary data sources. Primary data were obtained directly from the results of interviews with all informants, namely the vice chancellor II/vice chair II for finance at each Al Washliyah university in North Sumatra. Data analysis techniques are data collection, data reduction and drawing conclusions. Techniques to guarantee data validity are credibility, transferability, dependability, and confirmability testing. The results of this study concluded that Islamic values ​​on financial accountability at Al Washliyah College are the value of siddiq, the value of tabligh, the value of trust, the value of fatah, the value of sincerity and the value of deliberation which are used as the basis for carrying out financial management at the Al Washliyah College of North Sumatra.